Assessment of the Larvicidal Efficacy of the Hexane-Leaf-Extracts of Selected Tropical Plant Species - Bawo D. D. S; Ayodele A. Oyedeji; Patrick B. Solomon; Frankland O. Briyai; Jasper F. N Abowei (Budapest International Research and Critics University, 2020)
The proliferation of mosquito vector in tropical countries has increased the prevalence of malaria with high morbidity and mortality burden. This research is concerned with the biolarvicidal efficacies of Cassia alata, Microdesmis puberula¸ and Spilanthes filicaulis extracted with hexane solvent, and screened against mosquito larva. Results on the negative control had no mortality on the larvae compared to the positive control, which had total mortality (p<0.05). The C. alata plant extracts was the most active with LC50 value of 25.26 ppm, followed by; M. puberula (32.83 ppm), and S. filicaulis (36.46 ppm). Based on the outcome of the larvicidal bioassay, Hexane-leaf-extracts of all plants can be recommended for the formulation of biolarvicide due to their efficacies.